2014
DOI: 10.1038/ncomms5666
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule electroluminescence and photoluminescence of polyfluorene unveils the photophysics behind the green emission band

Abstract: Optoelectronic properties of polyfluorene, a blue light-emitting organic semiconductor, are often degraded by the presence of green emission that originates mainly from oxidation of the polymer. Here, we use single-molecule electroluminescence (EL) and photoluminescence (PL) spectroscopy on polyfluorene chains confined in vertical cylinders of a phase-separated block copolymer to spectrally resolve the green band and investigate in detail the photophysical processes responsible for its appearance. In both EL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 45 publications
2
62
4
Order By: Relevance
“…23,24 The use of single-molecule spectroscopy (SMS), with its unique ability to investigate polymer chains one by one, [25][26][27] has been particularly useful for the study of PFO because its intrinsic phase heterogeneity cannot be resolved by conventional ensemble-averaging spectroscopy. 25,[28][29][30] SMS studies of PFO molecules dispersed in a Zeonex matrix demonstrated the coexistence of aand b-phase chains at 5 K. 31 Considering the highly diluted nature of the samples used in these studies, it was concluded that b-phase formation does not need interchain interactions and that stress-induced backbone planarization could result from interactions with the host matrix. Similar SMS studies using matrix-embedded PFO oligomers have shown that b-phase formation is a molecular-length-dependent process and that nine or more repeat units are necessary to form a stable planarized structure, at least when prepared through the vapor-swelling procedure.…”
Section: Progress and Potentialmentioning
confidence: 94%
“…23,24 The use of single-molecule spectroscopy (SMS), with its unique ability to investigate polymer chains one by one, [25][26][27] has been particularly useful for the study of PFO because its intrinsic phase heterogeneity cannot be resolved by conventional ensemble-averaging spectroscopy. 25,[28][29][30] SMS studies of PFO molecules dispersed in a Zeonex matrix demonstrated the coexistence of aand b-phase chains at 5 K. 31 Considering the highly diluted nature of the samples used in these studies, it was concluded that b-phase formation does not need interchain interactions and that stress-induced backbone planarization could result from interactions with the host matrix. Similar SMS studies using matrix-embedded PFO oligomers have shown that b-phase formation is a molecular-length-dependent process and that nine or more repeat units are necessary to form a stable planarized structure, at least when prepared through the vapor-swelling procedure.…”
Section: Progress and Potentialmentioning
confidence: 94%
“…The FWHM values for the ONs are ≈25 nm, which is comparable to those of semiconductor quantum dots (30–40 nm). The minor peaks detected at longer wavelengths (≈30 nm) are attributed to the vibronic transitions of highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) states, which are typically observed in organic fluorophores . Furthermore, for the F‐, C‐, and N‐ON samples, relatively small emission bands appear in the 400–500 nm region, presumably due to oxygen‐containing defects.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, we note the presence of an emission band at longer wavelengths, i.e. a green band, which is common in F8-based emissive devices due to the formation of inter-chain states and/or fluorenone defects [37][38][39][40] . Importantly, the emissive bands of the three OSOLETs cover well both the visible region (400-700 nm) and even stretch into the near infrared (NIR) up to 800 nm.…”
Section: Characteristics Of Osoletsmentioning
confidence: 81%